IMPLEMENTATION OF THE INDIRECT DEFINITION IN THE RUSSIAN-UZBEK PHRASEOLOGICAL DICTIONARY (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article is devoted to the indirect definition, which belongs to the type of extended definitions and is quite often found in the Russian-Uzbek phraseological dictionary. Indirect description serves to indicate a typical situation in which a phraseological unit of the source language is used or to clarify the semantic content of which a wide context is required, representing a certain etymological reference.